Konsep Pendidikan yang Bermutu dalam Pengembangan Mutu Lembaga Sekolah - Fatimah, Meti; Pamungkas, Maulana Al Bana; Slamet, Slamet (Lembaga Yasin AlSys, 2025)
Education is something strategic and fundamental to the intellectual life of the nation. Improving the quality of education is one of the main pillars in building education in Indonesia. Quality education is education that is able to produce graduates who have the ability or competence, both academic competence, and vocational competence, which are based on personal and social competencies, as well as noble moral values, all of which are life skills. produce a complete human being (a complete human being) or a human being with an integral personality (integrated personality) capable of integrating faith, knowledge, and charity. There are several steps that must be done, namely a). Form a strong team, b). Confirming the vision, mission, and goals of the institution, c). Analyzing Problems, d). Determine the quality policy, e) Determine the quality standard, f). determine quality standards, g). determine the procedure. In implementing TQM in schools, the following aspects must also be considered: a). Learning services for students, b). Student management and services, c). Educational Facilities, d). School culture, e). Education Financing, f). Community attention and participation, g). Education Management.